Hydrogen sulfide (H2S) removal using schist packings in industrial biofilter applications - Shareefdeen, Zarook (2015)
Expanded schist can be a promising biofilter media for Hydrogen Sulfide (H2S) removal in industrial applications. In this work, H2S removal performance of a biofilter packed with expanded schist is compared with a patented (EU Patent No. 0 497 214 B1) media which has been commercialized and used in many industrial applications for odor and VOC control from contaminated airstreams. Hydrogen sulfide (H2S) removal performance data from two different schist packing media combinations were used in the analysis (BF1: inoculated with activated sludge, BF3: inoculated with activated sludge and 12% synthetic nutrient-UP20). Different mathematical models that describe H2S removal performance of a patented and schist packing media, respectively, were used to determine the limitations, similarities and differences of both media. The results show that both model predictions are in close agreement with the experimental data of schist packing that is inoculated with activated sludge (BF1). Thus, patented media removal performance of H2S is closely equivalent to expanded schist media inoculated with activated sludge (BF1). When model comparisons are made on a similar basis with schist media inoculated with activated sludge and 12% UP20 nutrient (BF3), the removal performance of schist media is found to be superior to that of patented biofilter media, especially for loading rate greater than 7 g/m3 media/hr. Since the patented biofilter media (EU Patent No. 0 497 214 B1) is commercially used by many industries, the results presented in this work will be valuable for practicing engineers and consultants who work in full-scale design and operation of biofilters.